¿Dónde está la deducción objetiva de Kant? - Osborne, Gregg (2007)
“Where Is Kant’s Objective Deduction?”. The preface to the first edition of Kant’s Critique of Pure Reason is marked by a distinction between objective and subjective sides of the transcendental deduction. The objective side alone is said to be essential to Kant’s main purpose and is also said to retain its full strength even if the subjective side is not found to be convincing. The thesis of this paper is twofold. First, that the most prominent accounts of this distinction in the literature are all subject to insuperable objections. Second, that the meat of the objective side is not to be found in the chapter explicitly devoted to the transcendental deduction but rather in the second chapter of the Analytic of Principles. What this implies is that a portion of the text frequently held to be the very heart of the Critique is said in the preface to the first edition to be inessential. We must therefore ask whether it is and be prepared to justify any divergence from the position espoused by Kant himself in 1781.